2003
DOI: 10.1021/om030182g
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected SN‘ Reaction on Cobaltocenium Triflates:  Substitution on One Ring and Elimination on the Other

Abstract: CpCo-capped tetra-n-propylcyclopentadienone complexes were O-alkylated and O-acylated. Reactions of the O-triflated product with organolithium compounds afford a substitution of the Cp ring in 40-80% yield; as products the RCpCo-capped tetra-n-propyl-cyclopentadienone complexes were isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In contrast to the ligand/H(Cp) exchange reaction of 27a initiated by HCl (Scheme 10), the reaction of 27a with PF 3 gave the product 43 resulting from the intramolecular insertion of carbene ligand into the C-H bond of the Cp ring (Scheme 15). 42d A similar carbene migration insertion into the indenyl ligand was also observed in reaction of (Z 5 -C 9 H 7 )RhQCPh 2 (P i Pr 3 ) (44) with CO, forming (Z 5 -C 9 H 6 CHPh 2 )Rh(CO)(P i Pr 3 ) (45). 46 Furthermore, it is found that nitrene can be inserted into the C-H bond of Cp ligand.…”
Section: Ring C-h Insertionsmentioning
confidence: 55%
See 1 more Smart Citation
“…In contrast to the ligand/H(Cp) exchange reaction of 27a initiated by HCl (Scheme 10), the reaction of 27a with PF 3 gave the product 43 resulting from the intramolecular insertion of carbene ligand into the C-H bond of the Cp ring (Scheme 15). 42d A similar carbene migration insertion into the indenyl ligand was also observed in reaction of (Z 5 -C 9 H 7 )RhQCPh 2 (P i Pr 3 ) (44) with CO, forming (Z 5 -C 9 H 6 CHPh 2 )Rh(CO)(P i Pr 3 ) (45). 46 Furthermore, it is found that nitrene can be inserted into the C-H bond of Cp ligand.…”
Section: Ring C-h Insertionsmentioning
confidence: 55%
“…Furthermore, a second n Bu group could be introduced at the b-position in the case of 33d (Scheme 12). 44…”
Section: Methodsmentioning
confidence: 99%
“…Gleiter and co-workers found it possible to protonate, to alkylate, and to acylate the oxygen center and then to create the corresponding cobaltocenium salts in good yields. 82 The protonation, alkylation, and acylation of the cyclopentadienone complex were carried out with CF 3 COOH, The Cp*-capped cobaltocenium monoacid and its derivatives can be synthesized from substituted Cp and a Cp*Co transfer reagent. Heck and co-workers reported the synthesis of (amino-η 5 -cyclopentadienyl)(1,2,3,4,5-pentamethylη 5 -cyclopentadienyl)cobalt(III) hexafluorophosphate (138) using cobalt transfer reagent Cp*Co(acac), while sodium (methoxycarbonyl)cyclopentadienide was used as the source for the second cyclopentadienyl ligand, as shown in Figure 36.…”
Section: Figure 34 Resonance Structures Of Cyclopentadienylcobalt-stabilized Cyclopentadienonesmentioning
confidence: 99%
“…102 The addition of triflate to the cyclopentadienone complex 328 has also been investigated, and this gives the cobaltocenium salt 329 in an 85% yield. 104 It was shown that further reaction with nucleophiles, such as MeLi or PhLi, does not yield the direct substitution product of the triflate, Scheme 90.…”
Section: Synthesis Using (Pr 3 ) 3 Cocl Complexesmentioning
confidence: 99%